Characterization of Organic Polymer Monolith Columns Containing Ammonium Quarternary As Initial Study For Capillary Chromatography - Aster Rahayu; Siti Jamilatun; Joni Aldilla Fajri; Lee Wah Lim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: The polymerization process with a simple step has become the centre of attention of several researchers. Various polymers have been developed, although in general, they use polymerization with a post-modification method. A quaternary ammonium monolith organic polymer has been prepared using a simple single thermal method in this research. 2-(Methacryloyloxy)-N,N,N-trimethylethanaminium chloride was as the monomer, and ethylene dimethacrylate was as crosslinker. The polymerization proceeded in fused-silica capillary (100 mm, 0.32 mm i.d. x 0.45 mm o.d.) using a one-pot approach method. To achieve the perfect macropores, isopropyl alcohol, PEG 400, and ethanol were used as porogen. Characterization of the surface morphology was carried out using a Scanning Electron Microscope (SEM), and the existence of an amine group was characterized by Fourier Transform Infrared Spectroscopy (FTIR). The distribution size of pores in the polymer was in the range of 1.29 to 3.33 µm.Abstrak: Polimerisasi dengan proses yang sederhana dan simpel menjadi pusat perhatian beberapa peneliti. Berbagai macam polimer telah dikembangkan, akan tetapi pada umumnya menggunakan polimerisasi dengan metode post-modification. Pada penelitian ini, polimer organik yang mengandung amonium kuartener dalam bentuk monolit dengan polimerisasi yang menggunakan suhu tunggal dan sederhana telah dilakukan. 2-(Methacryloyloxy)-N,N,N-trimethylethanaminium chloride digunakan sebagai monomer dan ethylene dimethacrylate sebagai crosslinker. Polimerisasi dilakukan dengan metode one-pot aaproach di dalam kapiler silika (100 mm, 0,32 mm i.d. x 0,45 mm o.d.). Untuk mendapatkan makropori yang sempurna, isopropil alkohol, PEG 400 dan etanol digunakan sebagai porogen. Karakterisasi morfologi permukaan dilakukan dengan menggunakan Scanning Electron Microscope (SEM), dan Fourier Transform Infrared Spectroscopy (FTIR) untuk mengidentifikasi gugus fungsi gugus amina yang terdapat pada polimer. Ukuran distribusi pori pada polimer berkisar antara 1,29 sampai 3,33 µm.